Approaching sexuality in LGBTQIAP + patients with cancer: scoping review - Tássia Santos Rodrigues; Ricardo Souza Evangelista Sant'Ana; João Paulo Zerbinati; Lucas Nascimento Souza; Anderson Reis de Sousa; Christine Maheu; Simone de Godoy (BMC, 2023)
Abstract Background When individuals in the SGM group are diagnosed with cancer and undergo treatment, they experience changes in physical, mental, sexual and spiritual dimensions, which can negatively impact sexual desire, as well as satisfaction and sexual health as a whole. This study aims to examine the existing scientific literature on how healthcare professionals approach sexuality in cancer patients who belong to the SGM group. The SGM group is particularly vulnerable, and the challenges they face in terms of psychosocial and emotional health are further exacerbated by the oncological treatment they receive. Therefore, specialized attention and support are necessary to address their unique needs. Method To conduct this study, a scoping review was performed following the guidelines established by the Joanna Briggs Institute. By synthesizing the available evidence, this study aims to provide insights and recommendations for healthcare professionals to improve the care and support provided to SGM individuals with cancer. Guiding question: "how do health professionals approach sexuality in cancer patients in a minority group?". The search was carried out in PubMed, Science Direct, Scopus, Web of Science, Virtual Health Library, Embase databases and Google Scholar in addition. Specific criteria were used for Evidence source selection, Data mapping, assurance, analysis, and presentation. Results Fourteen publications were included in this review for the final synthesis, which indicated that the approach to the sexuality of sexual and gender minority groups is based on research whose character is limited in terms of producing care and health care that is congruent in gender and sexuality. The analysis of scientific articles showed that one of the biggest challenges and priorities of health services today is to reduce disparities and promote equity in health for SGM people. Conclusions This study reveals a significant gap in addressing the sexuality of SGM groups within cancer care. Inadequate research impedes the provision of consistent and inclusive care for SGM individuals, which has a negative impact on their overall wellbeing. Reducing disparities and promoting healthcare equity for SGM individuals must be a top priority for health services.